Does contact with the justice system deter or promote future delinquency?: Results from a longitudinal study of British adolescent twins - Motz, Ryan T. (Criminology, 2020)
What impact does formal punishment have on antisocial conduct—does it deter or promote it? The findings from a long line of research on the labeling tradition indicate formal punishments have the opposite-of-intended consequence of promoting future misbehavior. In another body of work, the results show support for deterrence-based hypotheses that punishment deters future misbehavior. So, which is it? We draw on a nationally representative sample of British adolescent twins from the Environmental Risk (E-Risk) Longitudinal Twin Study to perform a robust test of the deterrence versus labeling question. We leverage a powerful research design in which twins can serve as the counterfactual for their co-twin, thereby ruling out many sources of confounding that have likely impacted prior studies. The pattern of findings provides support for labeling theory, showing that contact with the justice system—through spending a night in jail/prison, being issued an anti-social behaviour order (ASBO), or having an official record—promotes delinquency. We conclude by discussing the impact these findings may have on criminologists’ and practitioners’ perspective on the role of the juvenile justice system in society.